2012
DOI: 10.3109/00016489.2012.699197
|View full text |Cite
|
Sign up to set email alerts
|

Objective evaluation of neck muscle tension and static balance in patients with chronic dizziness

Abstract: Conclusion: Increase in the average value of bilateral neck muscle tension (ANT) indicates the increase in neck muscle tension to stabilize static posture resulting from vestibular compensation. Asymmetry of neck muscle tension was closely related to postural imbalance. Objective: Patients with dizziness often complain of neck symptoms with stiff neck. This study was conducted to clarify the pathophysiological mechanism of neck symptoms in patients with dizziness. Methods: We objectively measured bilateral tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…Other considerations are the potential for primary cervical afferent disturbances leading to secondary vestibular impairments, 37,97 primary vestibular or visual impairments influencing the cervical spine, 2,89,131 and the presence of concomitant cervical, visual, vestibular, and or mild brain deficits such as those seen following concussion.…”
Section: Clinical Assessmentmentioning
confidence: 99%
“…Other considerations are the potential for primary cervical afferent disturbances leading to secondary vestibular impairments, 37,97 primary vestibular or visual impairments influencing the cervical spine, 2,89,131 and the presence of concomitant cervical, visual, vestibular, and or mild brain deficits such as those seen following concussion.…”
Section: Clinical Assessmentmentioning
confidence: 99%
“…In the present study, we found that the relapsing remitting phases of UPVD were associated with HT. Asama et al (2012) showed that vestibular compensation for VCR occurred in patients with chronic dizziness, further increasing proprioceptive afference from the neck muscles to the vestibular nucleus, they believe that the asymmetry of the neck muscle tension could reflect the bilateral asymmetry of vestibular function, and the increase in the asymmetry of the neck muscle tension is intended to compensate for postural stability, that is, vestibular compensation can cause HT in patients after the peripheral vestibular function is impaired on one side. Further dynamic studies with a large sample size are needed to explore the relationship between HT and disease duration.…”
Section: F I G U R E 5 Correlations Between Vestibular Graviceptive P...mentioning
confidence: 99%
“…Najnovija istraživanja uz primjenu modernih uređaja (posturografija, konzola Nintendo Wii) pokazuju da tretiranje poremećaja ravnoteže može djelovati na smanjenje boli i povećanje pokretljivosti vrata. [26][27][28] U Krapinskim toplicama primjenjuju se dvije terapijske metode nastale kombinacijom nekoliko tehnika u tretmanu nespecifične boli u vratu. Jednu metodu provodi fizioterapeut kroz manipulaciju mišića vrata, trakciju i mobilizaciju vrata.…”
Section: Sudioniciunclassified